Standardized Precipitation Index Valuation of the Impact of Climate Variability and Change on Domestic Water Accessibility in Bamenda III Municipality, North West Region, Cameroon (Global Journal of Science Frontier Research, 2023)
The effects of climate variability and change are felt most at the household level, when taps and springs run dry for several weeks or months, forcing people to access potable water from doubtful sources. There has been an increase in the population of the Bamenda III municipality without a corresponding increase in the domestic water supply volume. This has resulted in severe water crises, even though Bamenda III municipality has water supplies from the council, community, CAMWATER, natural springs and streams, wells and boreholes. Data on water accessibility against a backdrop of climate variability and change was collected using 269 questionnaires. Rainfall data were collected from 1963-2019 and results revealed that mean annual rainfall is 182.52 mm, with a standard deviation of 29.16 and a coefficient of variation of 15.69%, while the mean Standardized Precipitation Index is -0.07 (mild dryness), and rainfall has reduced by -2.07 mm from 1963-2019. The population ascribed problems of water accessibility to climate variability and change, urbanization and poor water governance. It is recommended that sustainable water management through Nature-based Solutions and Ecosystembased Adaptation should be implemented from the watershed to the community level.
Keywords: adaptation; water security; vulnerability